Implementasi Metode Al-Masniari Pada Program Menghafal Al-Qur’an di SMP Shafiyyatul Amaliyyah - Agus Perry Hasibuan, Jen; Setiawan, Hasrian Rudi (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
This study aims to examine the implementation of the Al-Masniari method in the Qur'an memorization program at Shafiyyatul Amaliyyah Junior High School. The Al-Masniari method is a Qur'an memorization technique that emphasizes repetition and a deep understanding of Qur'anic verses. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation. The results show that the Al-Masniari method improves students' motivation and the quality of their memorization. The strength of this method lies in its systematic repetition approach, which has proven effective in helping students retain their memorization over the long term. The challenges in implementing this method include time constraints and limited specialized training for teachers. Overall, the Al-Masniari method is considered effective in enhancing Qur'an memorization skills among junior high school students. These findings are expected to contribute to the development of Qur'an memorization methods in various Islamic educational institutions.